New proaporphines from the bark of Phoebe scortechinii - Mukhtar, Mat Ropi; Hadi, A.H.A.; Rondeau, D.; Richomme, P.; Litaudon, M.; Mustafa, Mohd Rais; Awang, Khalijah (Taylor & Francis, 2008)
The phytochemical study of the bark of Malaysian Phoebe scortechinii (Lauraceae) has resulted in the isolation and identification of two new proaporphine alkaloids; (þ)-scortechiniine A (1) and (þ)-scortechiniine B (2) together with two known proaporphines;()-hexahydromecambrine A (3), ()-norhexahydromecambrine A (4), and one aporphine; norboldine (5). Structural elucidations of these alkaloids were performed using spectroscopic methods especially 1D and 2D 1 H and 13 C NMR.